(untitled) (Medico Legal Update, 2021)
Background: The main concern of universities is regarding the quality and effectiveness of education. A total of 32 dentistry faculties in Indonesia have implemented Problem Based Learning (PBL) classes in their learning curriculum. Some dentistry faculties have actively used student-centered learning method, and are no longer teacher-centered. According to the results of the 2017 Indonesian Internet Service Providers Association, the prevalence for Indonesian (Undergraduate/Diploma) students as Internet users reached 79.23%. Purpose: To describe the perception of Universitas Airlangga Faculty of Dental Medicine students on the effectiveness of the Problem Based Learning (PBL) class using the Online Learning method. Method: Data was collected from the distribution of questionnaires to students of Universitas Airlangga, Faculty of Dental Medicine semesters 1, 3, 5, and 7. Then a descriptive statistical test was conducted. Results: The percentage of respondents who considered effective Problem Based Learning (PBL) classes using online learning method was 52.4%, very effective at 5.8%, very ineffective at 2.9%, no opinion at 14.6%, and ineffective at 24.3%. Conclusion: The majority of Universitas Airlangga Faculty of Dental Medicine students have an effective perception of the Problem Based Learning (PBL) class using the Online Learning method.